Assumptions underpinning the conceptualization of professional learning in teacher education - Reeves, Cheryl; Robinson, Maureen (South African Journal of Higher Education, 2016)
This article outlines different approaches to the development of pre-service student teachers’ professional knowledge of and for practice. Key debates and positions are identified in the literature regarding aspects of the theory-practice relationship. These include different theories of knowledge and skills transfer, assumptions about the type of expertise future teachers should possess and about ‘what counts’ as the knowledge underpinning the practice of teaching, and different positions on the relationship between pedagogical knowledge and subject knowledge. The paper considers how these various conceptualisations and assumptions influence curriculum thinking, and how these are linked to contemporary debates and policy frameworks on teacher education in South Africa.